Functional inactivation of the orbitofrontal cortex disrupts context-induced reinstatement of alcohol seeking in rats - Bianchi, Paula Cristina [UNESP]; Carneiro de Oliveira, Paulo Eduardo [UNESP]; Palombo, Paola [UNESP]; Leao, Rodrigo Molini; Cogo-Moreira, Hugo; Planeta, Cleopatra da Silva [UNESP]; Cruz, Fabio Cardoso (Elsevier B.V., 2018)
Background: The high rate of relapse to drug use remains a central challenge to treating drug addiction. In human and rat models of addiction, environmental stimuli in contexts associated with previous drug use can provoke a relapse of drug seeking. Pre-clinical studies have used the ABA renewal procedure to study context induced reinstatement of drug seeking. In the current study, we studied the role of the orbitofrontal cortex (OFC) in context-induced reinstatement to alcohol. Methods: We trained male and female rats to self-administer alcohol in context A, extinguished drug-reinforced responding in a distinct context B, and assessed context-induced reinstatement in context A or B (control group). Next, we determined the effect of context-induced renewal of alcohol-seeking behavior on the expression of Fos (a neuronal activity marker) in the OFC. Finally, we determined the effect of reversible inactivation by GABAa and GABAb receptor agonists (i.e., muscimol and baclofen, respectively) in the OFC. Results and conclusions: There were no differences between male and female rats in context-induced reinstatement of alcohol-seeking behavior. Re-exposure to Context A, but not Context B, reinstated alcohol-seeking behavior and increased expression of the neural activity marker Fos in the OFC. Reversible inactivation of the OFC with muscimol and baclofen attenuated context-induced reinstatement. Our data indicated that the OFC mediates context-induced reinstatement of alcohol-seeking behavior.
Keywords: Alcohol self-administration; Orbitofrontal cortex; Male and female rats; Functional inactivation